Multispheroidal model of magnetic field of uncertain extended energy-saturated technical object - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Chunikhin, K. V.; Kolomiets, V. V.; Kobylianskyi, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The implementation of strict requirements for magnetic silence of elongated energy-saturated technical objects – such as naval vessel and submarines is largely determined by the adequacy of mathematical models to the signatures of a real magnetic field. Aim. Simplification of mathematical modeling of the magnetic field of an uncertain extended energy-saturated object based on the development and application of a multispheroidal model of its magnetic field instead of the well-known multidipole model. Methodology. Coordinates of the geometric location and magnitudes of spatial extended spheroidal harmonics of spheroidal sources of multispheroidal model of magnetic field calculated as magnetostatics geometric inverse problems solution in the form of nonlinear minimax optimization problem based on near field measurements for prediction far extended technical objects magnetic field magnitude. Nonlinear objective function calculated as the weighted sum of squared residuals between the measured and predicted magnetic field COMSOL Multiphysics software package used. Nonlinear minimax optimization problems solutions calculated based on particle swarm nonlinear optimization algorithms. Results. Results of prediction far magnetic field magnitude of extended technical objects based on designed multispheroidal model of the magnetic field in the form of spatial prolate spheroidal harmonics in prolate spheroidal coordinate system using near field measurements with consideration of extended technical objects magnetic characteristics uncertainty. Originality. For the first time the method for design of multispheroidal model of magnetic field of uncertain extended energy-saturated technical object based on magnetostatics geometric inverse problems solution and magnetic field spatial spheroidal harmonics calculated in prolate spheroidal coordinate system taking into account of technical objects magnetic characteristics uncertainties developed. Practical value. It is shown the possibility to reduce the number of spheroidal sources of the magnetic field for adequate modeling of the real magnetic field based on the developed multispheroidal model compared to the number of well-known dipole sources of the magnetic field in the multidipole model of the magnetic field.

Реалізація жорстких вимог щодо «магнітної тиші» витягнутих енергонасичених технічних об’єктів – таких як військові кораблі та підводні човни, значною мірою визначається адекватністю математичних моделей сигнатурам реального магнітного поля цих об’єктів. Мета. Спрощення математичного моделювання магнітного поля невизначеного видовженого енергонасиченого об’єкта на основі розробки та застосування мультисфероїдальної моделі його магнітного поля замість відомої мультидипольної моделі. Методологія. Координати геометричного розташування та величини просторових витягнутих сфероїдних гармонік сфероідальних джерел мультисфероїдальної моделі магнітного поля витягнутих технічних об’єктів розраховані як розв’язок обернених геометричних задач магнітостатики в формі нелінійної задачі мінімаксної оптимізації на основі вимірювань ближнього поля для прогнозування величини магнітного поля витягнутих технічних об’єктів. Нелінійна цільова функція розрахована як зважена сума квадратів залишків між виміряним і прогнозованим магнітним полем з використаням програмного пакету COMSOL Multiphysics. Розв’язки задач нелінійної мінімаксної оптимізації розраховані на основі алгоритмів нелінійної оптимізації рою частинок. Результати. Результати прогнозування величини віддаленого магнітного поля витягнутих технічних об’єктів на основі спроектованої мультисфероїдальної моделі магнітного поля в вигляді просторових витягнутих сфероїдальних гармонік в витягнутій сфероїдній системі координат з використанням вимірювань ближнього поля та з врахуванням невизначеності магнітних характеристик витягнутих технічних об’єктів. Оригінальність. Вперше розроблено метод проектування мультисфероїдальної моделі магнітного поля невизначеного витягнутого енергонасиченого технічного об’єкта на основі розв’язку геометричних обернених задач магнітостатики та обчислення просторових сфероїдальних гармонік магнітного поля в витягнутій сфероїальній системі координат з врахуванням невизначеності магнітних характеристик технічного об’єкта. Практична цінність. Показана можливість зниження кількості сфероідальних джерел магнітного поля для адекватного моделювання реального магнітного поля на основі розробленої мультісфероідальної моделі в порівнянні із кількістю дипольних джерел магнітного поля в відомій мультідипольній моделі магнітного поля.
Keywords: energy-saturated extended technical objects; magnetic field; multispheroidal model; magnetic silencing; extended spheroidal coordinate system; spatial extended spheroidal harmonics; енергонасичені витягнуті технічні об’єкти; магнітне поле; мультисфероїдальна модель; магнітна тиша; витягнута сфероїдна система координат; просторові витягнуті сфероїдні гармоніки